Proposed Curriculum for Physical Education to Elementary School for Girls in Saudi Arabia According to the American Education System - Awn, Abdulmohsen (My University, 2019)
The purpose of this proposal is to investigate and design Physical Education and Health-related curriculum programs for girls in Saudi Arabic elementary schools. The project will be implemented in two phases. The first phase is the initiatives for preparation and design (training packet) for female teachers on how to teach physical education and designing curriculum for girls. The second phase is for implementing the physical education curriculum after the preparation of a specialized curriculum for the students in the academic year 2019-2020. This quantitative study will employ two groups: an intervention group using American instructional methods for teaching physical education and the controlled group which will use the teaching instruction based on Saudi Arabia physical education for boys. Ten elementary schools for girls will be randomly selected based on school location (north, south, east, and west regions) in Riyadh. The goal for implementing physical education for girls at elementary schools is to help build fitness, improve health, develop social skills, and positively affect the appearance and psychological conditions for girls.
Keywords: Physical Education; Saudi girls; Health-released fitness; Motor skills